2016
DOI: 10.1530/eje-15-0640
|View full text |Cite
|
Sign up to set email alerts
|

Using subscales when scoring the Cushing's quality of life questionnaire

Abstract: Context: Patients in long-term remission of Cushing's syndrome (CS) commonly report impaired quality of life (QoL). The CushingQoL questionnaire is a disease-specific QoL questionnaire for patients diagnosed with CS. The developers of the CushingQoL recommend using a global (total) score to assess QoL. However, the global score does not capture all aspects of QoL as outlined by the World Health Organization (WHO). Objective: The aim of the study was to compare the performance of different scoring options to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…Recently however two subscales (psychosocial issues and physical problems) were identified, which showed adequate model fit. Data were obtained from patients in remission from CS (n = 341) recruited from the Cushing's Syndrome Research Foundation's email lists; they completed the CushingQoL questionnaire and a short demographics survey (54). Regardless of the scoring solution used, it was concluded that CushingQoL had proven to be a valuable resource for assessing healthrelated QoL in patients with CS.…”
Section: Cushing's Diseasementioning
confidence: 99%
“…Recently however two subscales (psychosocial issues and physical problems) were identified, which showed adequate model fit. Data were obtained from patients in remission from CS (n = 341) recruited from the Cushing's Syndrome Research Foundation's email lists; they completed the CushingQoL questionnaire and a short demographics survey (54). Regardless of the scoring solution used, it was concluded that CushingQoL had proven to be a valuable resource for assessing healthrelated QoL in patients with CS.…”
Section: Cushing's Diseasementioning
confidence: 99%
“…Patients in the present study were recruited by Tiemensma et al (2016), who examined different scoring options of the CushingQoL. A short message with a web link to the online survey was distributed to patients treated for CS through the Cushing's Support and Research Foundation's (CSRF) listserv and Facebook page.…”
Section: Methodsmentioning
confidence: 99%
“…Items are measured on a 5-point Likert-type scale assessing how often (Always to Never) or how much (Very Much to Not at All) each item has been related to the patient's CS in the previous 4 weeks. The CushingQoL provides insight into physical problems and psychosocial issues (Webb et al, 2008; Tiemensma et al, 2016). Scores for each of the subscales of the CushingQoL are summed and transformed to range from 0 (worst possible QoL) to 100 (best possible QoL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations